기존 건축물의 사용승인허가 전·후 거주환경을 고려한 화재피난성능평가 연구 - 김학경(Kim, Hak Kyung); 최두찬(Choi, Doo Chan); 김인태(Kim, In Tae); 김희문(Kim, Hee Moon); 심혜인(Sim, Hye In) (한국화재소방학회 논문지, 2016)
In Korea, fire hazard and risk analysis and response management planning related to existing decrepit buildings, including interior construction and architectural layout revision, due to various occupancy purposes have not been researched or established. Therefore, regulations and technical standards that can manage and reduce fire hazards and risks based on fire hazard analysis and evaluation are required. This study was performed based on a site survey and fire evacuation assessment including performancebased analysis in 3 actual existing buildings to find the life safety issues and provide improvement recommendations. 국내 건축물의 다양한 거주목적과 특성에 따른 재실자가 거주하게 됨에 발생되는 내부 인테리어 공사 등을 포함한 건축변경으로 인해 증대되는 화재위험성에 대한 분석과 대응은 미비하다. 건축피난성능이 저하된 기존 건축물이 늘어갈수록 화재사고가 발생할 가능성이 높아짐에 따라 체계적인 화재위험도평가를 수행하여, 화재위험을 저감하고 관리할 수 있는 제도적 장치와 평가기법을 개발이 필요하다. 본 연구는 그 첫 번째 과정으로서 기존 건축물 3개소에 대해서 1단계는 현장조사, 2단계는 화재피난성능평가를 진행하여 문제점을 분석하고 개선방안의 제안을 목적으로 진행하였다.